Association between renal function and cardiovascular and all-cause mortality in the community-based elderly population: results from the Specific Health Check and Guidance Program in Japan - Kon, Soichiro; Konta, Tsuneo; Ichikawa, Kazunobu; Asahi, Koichi; Yamagata, Kunihiro; Fujimoto, Shouichi; Tsuruya, Kazuhiko; Narita, Ichiei; Kasahara, Masato; Shibagaki, Yugo; Iseki, Kunitoshi; Moriyama, Toshiki; et al. (Clinical and experimental nephrology, 2018)
Background Chronic kidney disease is a significant risk factor for end-stage kidney disease, cardiovascular events, and premature death. However, the prognostic value of low estimated glomerular filtration rate (eGFR) in the elderly is debatable. Methods We determined eGFR using the Japanese equation in 132,160 elderly subjects (65–75 years) who attended the special health checkup (Tokutei-Kenshin) in 2008 and investigated the association between baseline eGFR and 5-year all-cause and cardiovascular mortality. Results The median (SD) eGFR was 70.5 ± 15.3 mL/min/1.73 m 2 . During follow-up, we noted 2045 all-cause deaths including 408 from cardiovascular events. A J-shaped curve was obtained when all-cause and cardiovascular mortality rates were compared with decreases in eGFR, with the highest mortality observed for eGFR <45 mL/min/1.73 m 2 . These trends were statistically significant in the Kaplan–Meier analysis ( P < 0.001). In the Cox proportional hazard analysis, after adjusting for possible confounders, those with eGFR <45 mL/min/1.73 m 2 , but not eGFR 45–59 mL/min/1.73 m 2 showed a higher all-cause and cardiovascular mortality than those with eGFR >90 mL/min/1.73 m 2 [hazard ratio (HR) 1.43, 95% confidence interval (CI) 1.06–1.91 for all-cause mortality, HR 2.28, 95% CI 1.28–4.03 for cardiovascular mortality]. Sex-based subgroup analyses showed similar results for both men and women. Conclusions We conclude that eGFR <45 mL/min/1.73 m 2 is an independent risk factor for all-cause and cardiovascular mortality in the elderly population.